Tiktok as social media marketing and the impact on purchase decisions - Clara Dwi Heska Fortuna (Marketing Management Studies, 2022)
This study aims to find out the Analysis Use of TikTok as Social Media Marketing, research how Purchasing Decisions, and research how the Use of TikTok as Social Media Marketing On Purchasing Decisions. The object of this study is Happy Go Lucky Bandung. The method used in this study is a descriptive and verification method, with data collection techniques that are the dissemination of questionnaires. Respondents in this study measured 100 customers Happy Go Lucky who used TikTok. The data used are primary and secondary data. The data technique used simple linear regression analysis with SPSS 25 software tools. The results showed that TikTok's ability as social media marketing against Purchasing Decisions was 73,3% as indicated by the coefficient of determination, while the remaining 26,7% was influenced by other factors not studied.